2022
DOI: 10.3390/molecules27030741
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Naringenin Nanosuspension and Its Antitussive and Expectorant Effects

Abstract: Naringenin (NRG) is a natural flavonoid compound abundantly present in citrus fruits and has the potential to treat respiratory disorders. However, the clinical therapeutic effect of NRG is limited by its low bioavailability due to poor solubility. To enhance the solubility, naringenin nanosuspensions (NRG-NSps) were prepared by applying tocopherol polyethylene glycol succinate (TPGS) as the nanocarrier via the media-milling method. The particle size, morphology, and drug-loading content of NRG-NSps were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…After optimizing the preparation conditions, the NRG NPs with a hydrodynamic diameter of 182.2 nm (PDI ~0.28) were obtained (Figure 1a). Transmission electron microscopy (TEM) results showed that the NRG NPs presented a sheet-like morphology (Figure 1b), which is consistent with our previous report [36].…”
Section: Particle Size and Morphologysupporting
confidence: 92%
See 1 more Smart Citation
“…After optimizing the preparation conditions, the NRG NPs with a hydrodynamic diameter of 182.2 nm (PDI ~0.28) were obtained (Figure 1a). Transmission electron microscopy (TEM) results showed that the NRG NPs presented a sheet-like morphology (Figure 1b), which is consistent with our previous report [36].…”
Section: Particle Size and Morphologysupporting
confidence: 92%
“…Among them, TPGS has been utilized broadly as a nanocarrier to encapsulate NRG, because of its excellent amphiphilic properties, entrapment efficacy, and biosafety [34,35]. In our previous study, we prepared the NRG nanoparticles (NPs) with TPGS as a drug carrier via wet media milling, and the obtained NRG NPs exhibited good antitussive and expectorant effects [36].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental reaction was carried out at 37°C. At a fixed time (5,15,30,45,60,75, 90 and 120 min), 0.2 mL samples were taken from each index at 8 different time points; the HPLC method was used to measure the dissolution rate of the samples and to draw the curve. The HPLC conditions were as follows: C18 column (4.6 × 100 mm 2 , 5 µm, Agilent LTD, Palo Alto, CA, USA).…”
Section: Dissolution Rate Analysismentioning
confidence: 99%
“…However, raw naringenin directly isolated from plants exhibits a poor dissolution rate and low bioavailability, which greatly limits its clinical application [14]. Dong et al reported that reducing the particle sizes of insoluble substances by increasing their specific surface area is an effective method for increasing dissolution rate [15]. The bioavailability of these substances is effectively increased by preparation with ultrafine technology [16].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation technology of NS can be divided into top-down and bottom-up methods [ 17 ]. In the top-down approach, two methods have been commonly used: wet stirred media milling (WSMM) and high-pressure homogenization [ 23 ]. WSMM is the most widely used and preferred method for preparing drug nanosuspensions because the top-down approach can efficiently produce small particles and does not require organic solvents, making them more viable in industrial production.…”
Section: Introductionmentioning
confidence: 99%